2019
DOI: 10.1177/2042098619854876
|View full text |Cite
|
Sign up to set email alerts
|

A pilot cohort study of deprescribing for nursing home patients acutely admitted to hospital

Abstract: Background: Patients from residential aged care facilities are commonly exposed to inappropriate polypharmacy. Unplanned inpatient admissions can provide an opportunity for review of complex medical regimens and deprescribing of inappropriate or nonbeneficial medications. The aim of this study was to assess the efficacy, safety and sustainability of in-hospital deprescribing. Methods: We followed a prospective, multi-centre, cohort study design, with enrolment of 106 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Albeit our sample size was relatively small ( n = 100), there was a signal of improved HRQOL, measured with Short Form-8, in those patients who had medications deprescribed. 17 As HRQOL is an important patient-centred endpoint, we addressed this issue in a larger patient population, using a different HRQOL measure, the EQ-5D-5 L, for ease of administration without loss of performance. We speculated that any improvement between 30 and 90 days post discharge would better reflect long-term medication changes made during the admission.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Albeit our sample size was relatively small ( n = 100), there was a signal of improved HRQOL, measured with Short Form-8, in those patients who had medications deprescribed. 17 As HRQOL is an important patient-centred endpoint, we addressed this issue in a larger patient population, using a different HRQOL measure, the EQ-5D-5 L, for ease of administration without loss of performance. We speculated that any improvement between 30 and 90 days post discharge would better reflect long-term medication changes made during the admission.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Deprescribing has already been shown to be safe in previous reports. In their pilot cohort study (n=106), Russell et al found a significant correlation between in-hospital deprescribing and improved quality of life without any signal of harm [8]. They did not find an association with readmissions, however.…”
Section: Discussionmentioning
confidence: 90%
“…This scoping review found that between 2009 and 2020, 20 studies (reported in 27 references) examined the effectiveness, safety and acceptability of deprescribing in older adults (aged ≥ 50 years) with polypharmacy (five or more prescribed medications) and multimorbidity (two or more long-term conditions) (see Appendix 3, Table 24 Material 1, Table 27; assessed effectiveness, impacts and outcomes for included studies are detailed in Report Supplementary Material 2, Table 28). [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] Of the 662 studies excluded at full-text stage, 148 were not explicit in stating or did not meet the number of multimorbidities [i.e. did not define their population as multimorbid (two or more long-term conditions), or reported mean/medians] and did not define or meet polypharmacy as being five or more drugs, 99 studies met the polypharmacy criteria (five or more prescribed medications) but did not meet/state the number of multimorbidities as two or more long-term conditions and 26 met the multimorbidity criteria but did not meet or define the polypharmacy criteria (see Report Supplementary Material 3, Table 29).…”
Section: Search and Screening Resultsmentioning
confidence: 99%